Talent Management and Public Sector Performance From the Perspective Of Federal Capital Territory (FCT) Abuja: An Evaluation Of The Ministry Of Education's Personnel Recruitment and Retention Strategies in Nigeria. - Ajiteru, S.A.R; Sulaiman, T.H; Abalaka, J.N (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The purpose of the Federal Capital Territory (FCT) of Abuja is to implement government directives in order to achieve national development goals. To accomplish this, recruitment and retention strategies in the civil service (CS) play a crucial role in providing the human resources needed. This study empirically investigates the recruitment and retention strategies applied in the FCT. The study utilized a survey method by distributing questionnaires to civil servants and conducting structured interviews to collect the necessary data to achieve the research objectives. To analyze the collected data, the study used the chi-square analytical technique. The findings reveal that the recruitment strategy in the CS is based on a combination of political and merit-based factors. Regarding employee retention, the study found that the CS has implemented relatively effective incentives to retain its workforce. However, while these incentives are sufficient for short-term retention, they are inadequate to retain skilled employees compared to the incentives offered by private companies. The recommendations from this study suggest that, in order to maintain a skilled workforce and enhance performance, the CS must implement more competitive incentives that are comparable to those offered by the private sector in order to attract and retain the best talent in the long run.